(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
In this work, we focus on the ways in which some teachers of basic technical and technological education (EBTT) create their self-construction itineraries through the possibility of envisioning their subjectivation processes and their influence, if any, on woven relationships by teachers between their personal trajectories and training and work, having as methodological basis the conversations stimulated by a semi-directive interview script. We bring reports that have caught our attention since they were produced by the ten teachers from a federal school who have already worked, or still work, in secondary education integrated with the technician. As a theoretical framework to talk with our research partners, we will adopt Michel Foucault’s thinking, using as a framework for the discussion proposed in this paper the techniques of subjection imposed by neoliberal governmentality and the confrontations with which teachers are faced.